MANAJEMEN KONFLIK NABI MUHAMMAD SAW : (Analisis Teks Sirah Ibnu Hisham dan Sirah Nabawi Ibnu Kathir) - Fathurrofiq rofiq (Jurnal Al I'jaz, 2022)
How the Prophet Muhammad managed the conflicts challanged his revealing massage is the main issue disscussed in this paper. Of course the conflict trigered by the brutal rejection of unbelievers to thethe Prophet teachings. Nevertheless, it didn’t mean that the conflicts was never come from the follower of the prophet at all. While the conflict rising from the followers threatened the segregetion and uncorfortable communication among them, the conflicts rising from the unbelivers cause the fatal condition even the war break. As The Prophet, Muhammad respond the conflict in all cost. But the special one is his ways, his manner to deal with such conflict. He never gave up to motivate his follower to keep alert, he never fail in hopeless in all nightmare condition he faced. His strategy to conduct the conflict, minimally, devided into two: 1)unapproachable integrity dealing with the belief, 2)flexible decission dealing with the socio-political bussiness. Let’s see the former in the case of ritual negosition offered by Quraish unbelievers to the Prophet then the later to the Hudaibiyah compropmy. This paper based on the reading on work of Ibnu Hisham: Sirah Nabawi and work of Ibnu Kathir: Sira Rasul. The both works are translated into English. So the explanation of this paper based on these work either in Arabic or in English.